Effects of a School‐Based Pedometer Intervention in Adolescents: 1‐Year Follow‐Up of a Cluster‐Randomized Controlled Trial. (10th September 2018) - Isensee, Barbara; Suchert, Vivien; Hansen, Julia; Weisser, Burkhard; Hanewinkel, Reiner
ABSTRACT: BACKGROUND: Physical activity (PA) is one of the most important health behaviors that may be modified by each individual. To foster PA in adolescents, a school‐based intervention was evaluated. METHODS: A cluster‐randomized controlled trial with preassessment in 2014 and follow‐up assessment in 2015 included 29 schools with 1020 students (47.6% girls, mean age = 13.69 years). Intervention students received pedometers and monitored their steps for 12 weeks. Classes with the most steps were awarded. Primary outcomes included moderate‐to‐vigorous PA, out‐of‐school sports activities, active transport assessed through questionnaires, as well as cardiorespiratory fitness measured using the 20‐m shuttle‐run test and anthropometric data (weight, height, body fat, and waist circumference) assessed by study staff. RESULTS: Significant interaction terms between group and time were found for all 3 indicators of PA; intervention students showed a higher increase of PA than control students. The same pattern was shown for cardiorespiratory fitness, but the effect missed significance. A more favorable development for the intervention students was shown for body fat and waist‐to‐height ratio, while there was no effect on body mass index percentile. CONCLUSIONS: An easy way to administer school‐based PA program may enhance students' leisure‐time PA even 1 year after the intervention has ended.